2018
DOI: 10.1115/1.4041682
|View full text |Cite
|
Sign up to set email alerts
|

Semi Analytical Solution of Heat Transfer of Magnetohydrodynamic Third-Grade Fluids Flowing Through Parallel Plates With Viscous Dissipation

Abstract: This study deals with the heat transfer characteristics of magnetohydrodynamic (MHD) flow of a third-grade fluid through parallel plates, subjected to a uniform wall heat flux, but of different magnitudes. The effect of viscous dissipation has been included for both heating and cooling of the fluid. The least square method (LSM) has been adopted for solving the nonlinear equations. The expressions for the velocity and temperature fields have been derived which, in turn, is utilized to evaluate the Nusselt numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Boundary conditions, required for solving Equation (44) and Equation ( 45) are the same as given by Equation (27) and Equations (28.1)- (28.3). Using Equations ( 44) and ( 45), the following equation involving only one variable u* is obtained:…”
Section: Solution For the Case Of Newtonian Fluidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Boundary conditions, required for solving Equation (44) and Equation ( 45) are the same as given by Equation (27) and Equations (28.1)- (28.3). Using Equations ( 44) and ( 45), the following equation involving only one variable u* is obtained:…”
Section: Solution For the Case Of Newtonian Fluidsmentioning
confidence: 99%
“…The technique may therefore have promising applications ranging from drug delivery, small size heat exchangers, and power generation to bio-medical devices, and so on. Some of the studies on EHD and MHD may be found in References [23][24][25][26][27][28][29][30][31][32]. In mixed convection flow and heat transfer also, the magnetic field can play a vital role by interacting with the complicated flow dynamics of the phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…Hayat et al [16] discussed the impacts of binary chemical reactions and activation energy on the third grade nanofluid with hydro magnetic flux with convective conditions. Chaudhuri et al [17] investigated thermal transfer properties of magnetohydrodynamic (MHD) that is subjected to a uniform thermal flux in the wall, but of varying magnitudes, of a third-grade fluid between parallel plates. Hayat et al [18] explore the characteristics of a magnetohydrodynamic third-grade nanofluid with triggering energy and binary chemical reactions.…”
Section: Introductionmentioning
confidence: 99%